DNA-mediated formation of phase-separated coacervates of the nucleic acid-binding domain of TAR DNA-binding protein (TDP-43) prevents its amyloid-like misfolding - Patni, Divya; Patil, Anjali D.; Kirmire, Mona S.; Jha, Anjali; Jha, Santosh Kumar (ACS Chemical Neuroscience, 2024)
Sequestration of protein molecules and nucleic acids to stress granules is one of the most promising strategies that cells employ to protect themselves from stress. In vitro, studies suggest that the nucleic acid-binding domain of TDP-43 (TDP-43tRRM) undergoes amyloid-like aggregation to beta-sheet-rich structures in low pH stress. In contrast, we observed that the TDP-43tRRM undergoes complex coacervation in the presence of ssDNA to a dense and light phase, preventing its amyloid-like aggregation. The soluble light phase consists of monomeric native-like TDP-43tRRM. The microscopic data suggest that the dense phase consists of spherical coacervates with limited internal dynamics. We performed multiparametric analysis by employing various biophysical techniques and found that complex coacervation depends on the concentration and ratio of the participating biomolecules and is driven by multivalent interactions. The modulation of these forces due to environmental conditions or disease mutations regulates the extent of coacervation, and the weakening of interactions between TDP-43tRRM and ssDNA leads to amyloid-like aggregation of TDP-43tRRM. Our results highlight a competition among the native state, amyloid-like aggregates, and complex coacervates tuned by various environmental factors. Together, our results illuminate an alternate function of TDP-43tRRM in response to pH stress in the presence of the ssDNA.
Keywords: amyloid-likeaggregation; complex coacervation; DNA-protein interactions; Dynamics; pH stress; TDP-43